Assessing the Suitability of Fifth Grade Textbooks on 'Ecosystems and Our Environment' in Lebong Elementary Schools - Guntur Gunawan; Andri Aprillia; Yosi Yulizah; Yuyun Yumiarty (STAI Hubbulwathan Duri, 2024)
This descriptive-quantitative study examines the eligibility of Grade 5 student textbooks on the theme of ecosystems and the environment at Lebong Regency Elementary School, using survey and observation to collect data and analyze it quantitatively. Lebong District's 93 elementary schools, including 180 fifth-grade teachers, are sampled using regional sampling, a random selection technique taken per sub-district. The study's main data is gathered through a questionnaire and secondary data from sources like textbooks for class IV students on the theme of